Morphological analysis of Mahabad river channeland the impact of Dam construction - hadi nayyeri (تحقیقات کاربردی علوم جغرافیایی)
The subject of the study is to analysis pattern of Mahabad River channel. This area is located on the south of Uromia Lake. Rapid changing of its channels pattern is an important characteristics which the evaluation of these characteristics is necessary to any hmplementation of development projects. For this purpose, the morphological changes of river channel were recognized by the areal photographices and satellite imageduring different times periods. The relationship between effective variables on the channel pattern such as, discharge, slope, stream power,stream bank clay content and width of bed, and observed pattern changes were analyses. The results showed that formation of braising channels could be the result of accumulation of bank coarse materials and increasing of width to depth ratio. The pattern of the river changed to sinuosity at the downside of braiding channel.the increased discharge and more river bank resistance due to high clay content caused to river pattern changed from breading to sinocity.In the distance between Mahabad dam at the upstream and diversion dam at the downstream, the river pattern was changed to Anabaranching. Assessment and comparison of Arial photographs before and after of Mahabad dam construction revealed that these types of channels were developed recently. Reduction of peak flows and sediment deposition in the channel as the result of dam construction, prepared the essenssial conditions to form Anabrancing